Techahealth's Digital Technology Based Collaborative Intranatal Care Model for Optimizing Healthy Births in Stunting Prevention - Yuliana ‎; Idawati ‎‎; Azhar Mualim; Irnawati ‎; Meliani Sukmadewi Harahap (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Stunting is a chronic nutritional problem that has a long-term impact on the quality of human resources and needs to be prevented from the beginning of life. The delivery process is a crucial phase in determining the baby's initial condition through the quality of intranatal care, the prevention of complications, and the success of early breastfeeding initiation (IMD). However, the practice of intranatal care in health care facilities still faces obstacles in the form of suboptimal collaboration between professions and the use of digital technology. This study aims to analyze the influence of the TECH4HEALTH Digital Technology-Based Collaborative Intranatal Care Model on the optimization of healthy births in stunting prevention. This study uses a quasi-experimental design with a pretest–posttest with control group. The sample consisted of 80 maternity mothers who were divided into an intervention group (n=40) and a control group (n=40). The intervention group received collaborative intranatal care based on digital TECH4HEALTH technology involving midwives, doctors, nurses, and nutritionists, while the control group received conventional intranatal care. The research variables included the quality of intranatal care, the success of IMD, the incidence of asphyxia, the baby's birth weight, and the level of maternal understanding of stunting prevention. The results showed a significant improvement in the quality of intranatal care in the intervention group with an average score increasing from 72.4 to 88.6 (p<0.001), while the control group only increased from 73.1 to 76.5. The success of IMD in the intervention group reached 87.5% compared to 62.5% in the control group. The incidence of asphyxia decreased to 5% in the intervention group compared to 17.5% in the control group, and the proportion of infants with normal birth weight was higher (92.5% vs. 77.5%). The level of maternal understanding of stunting prevention increased significantly (p<0.001) after the application of the TECH4HEALTH model.